Characterization of digestive enzymes from captive Brazilian flounder Paralichthys orbignyanus - Candiotto,F. B. (2018)
Abstract Knowledge of specific enzyme activity, along with animal habits and digestive capacity is essential in formulating an appropriate diet for any species. In this study, we evaluated and characterized the activity of digestive enzymes present in the liver, intestine, and stomach of Paralichthys orbignyanus. The effects of pH and temperature on enzyme activity were also evaluated via the use of specific substrates. The use of specific substrates and inhibitors showed strong evidence of the presence of trypsin (BApNA= 0.51 ± 0.2 mU mg-1), chimotrypsin (SApNA= 2.62 ± 1.8 mU mg-1), and aminopeptidases (Leu-p-Nan =0.9709 ± 0.83 mU mg-1) in the intestine. Optimum pH for the activity of trypsin, chemotrypsin, leucino aminopeptidase, amilase, and pepsin were 9.5, 9.0, 8.0, 7.5, and 3.5, respectively, while optimum temperatures were 50, 50, 50, 40, and 45 °C, respectively. These results provide additional information regarding the biology of Brazilian flounder and can be used as a basis for further studies regarding fish feeding physiology.